Perlindungan Hukum Bagi Peserta BPJS Kesehatan Yang Melakukan Pembayaran Premi Melalui Payment Point Online Bank ( PPOB ) di Desa Tanjung Bungo Kecamatan Kampa - Oktaviani Aswar; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Health insurance is held with the aim of ensuring that participants receive health care andprotection benefits in meeting basic health needs. But BPJS Health participants in this case manyexperienced complaints because of the late Payment Point Online Bank (PPOB) paying participants'contributions to BPJS Health. The purpose of this essay is: First, the implementation of legal protection forBPJS Health participants who make premium payments through Payment Point Online Bank (PPOB) inTanjung Bungo Village, Kampa Subdistrict, Secondly, constraints and efforts made by BPJS HealthParticipants who make premium payments through Payment Point Online Bank (PPOB) in Tanjung BungoVillage, Kampa District.This type of research is a type of sociological legal research. This research was conducted at thePekanbaru Branch BPJS Health office JL. Tuanku Tambusai Ujung Komp. 20 Ruko No. 6F-10J Ex.Labuhbaru Barat Kec. Umbrella City of Pekanbaru. While the population and sample are the Head ofPublic Communication BPJS, BPJS Health Participants, and PPOB. The data used are primary data,secondary data and tertiary data and data collection techniques are field studies, interviews, and literaturestudies.The results of the problem research are two main things that can be concluded. First, theimplementation of legal protection for BPJS Health participants who make premium payments throughPayment Point Online Bank (PPOB) in Tanjung Bungo Village, Kampa Subdistrict does not work inaccordance with applicable laws and regulations, namely that everyone has the right to get health services,benefits health and protection in meeting basic health have not been fully obtained by participants. Second,the constraints and efforts made in implementing legal protection for BPJS Health participants who makepremium payments through Payment Point Online Bank, the obstacle experienced by the PPOB is the lackof openness and caution in accepting and paying participant contributions and the existence of networkdisruption in terms of deposits to the BPJS Kesehatan, while from the participants there was a lack ofknowledge of participants regarding the rights they should have obtained.Keywords: Legal Protection-BPJS Participants Health-Payment Point Online Bank